DESKRIPSI LANGKAH-LANGKAH TIPE STAD DALAM RPP TEMATIK KELAS V SEKOLAH DASAR - Petronela Maria Ria Alma; Siti Halidjah; Rio Pranata (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract The study aims to describe the suitability of the content of each component in the implementation plan of thematic learning referring to the Permendikbud 22 of 2016 on Process Standards and to describe the suitability of STAD types. The research method used is a descriptive qualitative method with the form of case study research. The primary data source is the teacher grade V SDN 66 and the secondary data source is the observation guidelines, interview guidelines, and the learning implementation plan sheet. The data collection techniques used in this study are indirect observation techniques, direct communication techniques, and documentary studies. Data collection instruments are researchers themselves using observation guidelines, interview guidelines, and implementation plans of learning theme 1 sub theme 1 learning 3, learning 4, and theme 2 sub theme 1 learning 3. Based on the observation data, interview results, and learning implementation plan obtained results, there are several components that are appropriate and also some are not suitable. The components of learning method selection and learning resource selection in accordance with the objectives, materials, and characteristics of learners in accordance with the Permendikbud 22 of 2016 and clarity of learning steps that apply the type of STAD. Keywords: Component, Learning Implementation Plan, Learning Steps, Student Teams-Achievement Divisions Type, Permendikbud